Clinical outcome of recurrent endometrial cancer: analysis of post-relapse survival by pattern of recurrence and secondary treatment. Issue 2 (1st December 2019) - Legge, Francesco; Restaino, Stefano; Leone, Luca; Carone, Vito; Ronsini, Carlo; Di Fiore, Giacomo Lorenzo Maria; Pasciuto, Tina; Pelligra, Silvia; Ciccarone, Francesca; Scambia, Giovanni; Fanfani, Francesco
Abstract : Introduction: Recurrence of endometrial cancer is an important clinical challenge, with median survival rarely exceeding 12 months. The aim of this study was to analyze patterns of endometrial cancer recurrence and associations of these patterns with clinical outcome. Methods: The study included patients with endometrial cancer who underwent primary surgical treatment with or without adjuvant treatment between July 2004 and June 2017 at the Gynaecologic Oncology Unit of one of three tertiary hospitals of the Catholic University Network in Italy with complete follow-up data available. Information on the date and pattern of recurrence was retrieved for each relapse. Post-relapse survival was recorded as the time from the date of recurrence to the date of death or last follow-up. Survival probabilities were compared using log rank tests, and associations of clinico-pathological characteristics with post-relapse survival were tested using Cox's regression models. Results: A total of 1503 patients were included in the analysis. We identified 210 recurrences (14.0%) and 105 deaths (7.0%) at a median follow-up of 34 months (range 1–162). One hundred and fifty-eight recurrences (78.1%) occurred during the first two years of follow-up. Most recurrences were multifocal (n=121, 57.6%) and involved extrapelvic sites (n=38, 65.7%). Parameters associated with post-relapse survival in the univariate analysis included histotype, grade, time to recurrence, pattern of recurrence, number of relapsing lesions, and secondary radical surgery. Only the pattern of recurrence and secondary radical surgery were independent predictors of post-relapse survival in the multivariate analysis (p=0.025 and p=0.0001, respectively). Conclusion: Lymph node recurrence and the feasibility of secondary radical surgery were independent predictors of post-relapse survival in patients with recurrent endometrial cancer.